Effects of Surface Properties of Rocky Areas on Overland Flow Generation in an Arid Area - Aaron Yair; Eran Meiri; Hanan Ginat (Current Advances in Geography, Environment and Earth Science Vol. 1, 2021)
Overland flow is usually regarded as an important contributor to channel flow. This approach is certainly valid in arid watersheds, where base flow is irrelevant, especially in small watersheds, where non-climatic factors such as lithology, topography, and local surface properties can exert a strong influence on overland flow generation. Understanding overland flow generation in dryland areas is therefore especially important, as rainfall thresholds for streamflow generation are highly dependent on the frequency and magnitude of overland flow generation. A relatively large literature is available for semi-arid areas. In some of these studies it is clearly stated that despite the lower average annual rain amount, the frequency and magnitude of channel flow is higher in the drier than in the semi-arid, wetter areas. This is attributed to a more extensive soil and vegetation cover in the wetter areas. Nevertheless, our knowledge on the complex factors that control overland flow generation, the main contributor to channel flow in extremely arid areas, (below 50 mm average annual rainfall) are very rare. The main objective of the present work is to obtain accurate data on runoff generation, in an extremely arid area ( 28 mm average annual rainfall), under natural rainfall conditions in a variety of geological formations and surface properties. The study was based on a couple of small runoff plots ( 3 m2) in each of the following lithologies: Limestone, Granite, Sandstone and Siltstone. One plot represents a rocky surface, and the second a colluvial surface. The study lasted two consecutive years. Data obtained showed that the frequency and magnitude of runoff generation, in each of the lithologies, were always higher over the rocky plots than over the colluvial plots. However, runoff generation was not uniform in the rocky, and in the colluvial plots. This is due to the local surface characteristics of each plot, such as stoniness and surface roughness. Data obtained bring us back to two important issues in geomorphology. The first is the possibility to extrapolate data from one area to another area with the same rainfall regime. The second issue is the relative geomorphic importance of frequent rain events versus rare geomorphic events.